KADAR SERAT, AKTIVITAS ANTIOKSIDAN, VISKOSITAS DAN SIFAT SENSORIS JELLY DRINK SUSU KECAMBAH KEDELAI DENGAN VARIASI KONSENTRASI DAUN CINCAU HIJAU - amrullah, Rully Amrullah; Aminah, Siti; Suyanto, Agus (Jurnal Pangan dan Gizi, 2024)
Soybeans have a fairly high protein content. The derivative product of soybean sprouts is soy sprouted milk. One of the product developments from soy sprouted milk is a jelly drink. This requires additional ingredients that function as jellying agents. Cyclea barbata leaves are one of the natural jellying agents, besides that green jelly is high in fiber and rich in antioxidants. The purpose of this study was to determine the effect of Cyclea barbata concentration on fiber content, antioxidant activity, viscosity, and sensory jelly drink of soy sprouted milk. This study used a single-factor Complete Randomized Design (RAL), namely the concentration of green grass grass leaves (2%,3%,4%,5%,6%). The variables analyzed were fiber content, antioxidant activity, viscosity, and sensory (hedonic quality). The results of this study showed that the concentration of Cyclea barbata leaves had a significant effect on fiber content, antioxidant activity, viscosity, and sensory (taste, color, texture), but did not have a real effect on sensory (aroma). The best treatment is at a concentration of green jelly leaves of 6% with a value of fiber content of 7.83%, antioxidant activity of 14.95%, viscosity of 4.70 mpa.s, and sensory 3.43 (close to like).